Genome-wide analysis of the WRKY gene family unveil evolutionary history and expression characteristics in tomato and its wild relatives - Liu, Guan; Zhang, Dongye; Zhao, Tingting; Yang, Huanhuan; Jiang, Jingbin; Li, Jingfu; Zhang, He; Xu, Xiangyang (Frontiers in Genetics, 2022)
WRKY transcription factors (WRKYs) are one of the largest plant gene families in plants involved in various biotic and abiotic stress responses. Based on the conservation of WRKY proteins, we identified a total of 642 WRKYs in Amborella trichopoda (33), Vitis vinifera (64), Arabidopsis thaliana (48), Solanum lycopersicoides (88), S. pennellii (77), S. pimpinellifolium (80), S. lycopersicum var. cerasiforme (85), S. lycopersicum cv. Heinz1706 (85), and S. lycopersicum cv. M82 (82) genomes. Phylogenetic analysis clustered WRKYs from nine genomes above into two clusters (Cluster1 and Cluster2). Evolutionary analysis revealed that most of the WRKYs in tomato and its wild relatives were expanded after the whole genome triplication (WGT) event of Solanum ancestor. Effects of tandem duplication (TD) event for WRKYs revealed that several WRKYs have experienced TD event and drove the expansion of the WRKY gene family in tomato and its wild relatives. Comparative analysis of WRKYs derived from WGT and TD events indicated that the WGT event performed a stronger influence on the expansion of the WRKY gene family than the effects of the TD event. Transcriptome profiling of WRKYs in S. lycopersicum cv. Heinz1706 under the biotic stress condition relative to the control condition uncovered a number of up-regulated WRKYs in response to biotic stress. The diversified expression pattern among paralogs derived from TD and WGT implied the impact of gene duplication events on gene functional divergence and diversity in tomato. We hope that this project will supply novel knowledge for studying the evolutionary history and functional characteristics of WRKYs involved in biotic stress in tomato.